The regulation of pyroptosis by post-translational modifications: molecular mechanisms and therapeutic targets - Yi-Rao Zhou; Jun-Jie Dang; Qi-Chao Yang; Zhi-Jun Sun (EBioMedicine)
Summary: Pyroptosis, a type of programmed cell death mediated by gasdermin family proteins, releases a large amount of immune stimulatory substances, which further contribute to inflammation and elicit an adaptive immune response against tumours and pathogens. And it occurs through multiple pathways that involve the activation of specific caspases and the cleavage of gasdermins. Post-translational modifications (PTMs) could influence the chemical properties of the modified residues and neighbouring regions, ultimately affecting the activity, stability, and functions of proteins to regulate pyroptosis. Many studies have been conducted to explore the influence of PTMs on the regulation of pyroptosis. In this review, we provide a comprehensive summary of different types of PTMs that influence pyroptosis, along with their corresponding modifying enzymes. Moreover, it elaborates on the specific contributions of different PTMs to pyroptosis and delves into how the regulation of these modifications can be leveraged for therapeutic interventions in cancer and inflammatory diseases.